Evaluation of medication adherence and treatmentsatisfaction İn patients using direct-acting oral anticoagulants - TEZCAN, SONGÜL (My University, 2023)
The aim of our study is to evaluate the medication adherence and satisfaction with anticoagulant treatment in patients using direct-acting oral anticoagulants (DOAC) in the cardiology outpatient clinic and the possible factors affecting it. This study was conducted in a cardiology outpatient clinic between May 2022 and September 2022. A total of 200 patients who applied to DOAC and used it before or started using it were included in the study. Duke anticoagulant satisfaction scale (DASS) and five-item Medical Compliance Report Scale (MARS5) were administered to each patient once, on the day of enrollment of the patients. The Turkish reliability and validity of these two scales were made and permissions for use were obtained [1,2].The mean age of the patients was 65.9±0.8 (range: 34-94), mean body mass index (BMI) was 28.9±0.4 (16-50).It was concluded that the higher the score a patient received from DASS, the less satisfied he was with his treatment. On the other hand, as the score increased in the scale of reporting drug compliance, it was revealed that the patient was compliant with the treatment.MARS-5 mean score was calculated as 20.8±0.3 (5-25). DASS mean score was calculated as 82.9 ±1.6 (25-175). It was determined that there was an inverse correlation between MARS-5 and the totalscore of the DASS, which wasstatistically significant (Spearman's rho=-0.42, p<0.0001). Although there was no significant difference between the DOAC active ingredients, rivaroxaban had the highest drug compliance. Patients applying to an outpatient cardiology clinic who used DOACs exhibited low levels of medication adherence and anticoagulant satisfaction, according to findings from 200 patients. It is anticipated that clinical pharmacy services may positively influence the health outcomes of both the control and study groups.
Keywords: Cardiology; Direct Acting Oral Anticoagulant; Medication Adherence; Duke Anticoagulant Satisfaction Scale